Alternative models of higher education: an epistemological enquiry - Isahak, Aldila (IPPTN, 2013)
This chapter explores the alternative models of higher education for Muslim universities globally. The epistemological enquiry which analyses three contemporary models of Islamization of Syed Muhammad Naquib al-Attas, Ismail Farooqi and IIUM led to the conclusion that the alternative models of higher education should be based on two: i. for undergraduate programme- IIUM should be the model and ii. for postgraduate programme- ISTAC that was under al-Attas should be the model.